2002
DOI: 10.1524/ract.2002.90.3_2002.127
|View full text |Cite
|
Sign up to set email alerts
|

Chemical isolation of dubnium (element 105) in fluoride media

Abstract: Element 105 / Dubnium / Fluoride / Ion exchange chromatographySummary. The isotope 262 Db was produced by irradiation of a 248 Cm target with 106-MeV 19 F ions at the 15 MV MP Tandem accelerator of Orsay (France). The reaction products were continuously and rapidly transported with a KCl aerosol helium jet system to the chemistry setup. They were dissolved in HF medium and the solution was passed through three successive ion exchange columns, allowing a continuous high level purification of Db from actinides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…First experiments have been performed with Rf to study the fluoride complexation [158,159,161] and with Db. [163,164] Rf and Db, transported by the He(KCl) jet to the chemistry apparatus, were continuously dissolved, and this solution was passed through three consecutive ion-exchange columns. Primary produced divalent and trivalent actinides were "filtered" out on the first cation-exchange column.…”
Section: Perspectives Of New Technological Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…First experiments have been performed with Rf to study the fluoride complexation [158,159,161] and with Db. [163,164] Rf and Db, transported by the He(KCl) jet to the chemistry apparatus, were continuously dissolved, and this solution was passed through three consecutive ion-exchange columns. Primary produced divalent and trivalent actinides were "filtered" out on the first cation-exchange column.…”
Section: Perspectives Of New Technological Developmentsmentioning
confidence: 99%
“…[202,205] The fluoride complexation of Db in 0.2 m HF was recently confirmed in an experiment which used three consecutive ion-exchange columns-a cation exchange (filter) column, an anion exchange (chromatography) column, and another (filter) cation exchange column. [163] It was shown that Db forms an anionic fluoride complex which is strongly retained on the anion-exchange resin.…”
Section: Liquid-phase Chemistrymentioning
confidence: 99%
“…Das chemische Verhalten von Transactinoiden wird später aus dem Verhältnis der langlebigen Tochteraktivitäten in der einen oder anderen Fraktion bestimmt. Erste Experimente sind mit Rf zur Untersuchung der Fluorid‐Komplexbildung158, 159, 161 und auch schon mit Db durchgeführt worden 163. 164 Die mit einem He(KCl)‐Jet zu der Chemieapparatur transportierten Rf‐ und Db‐Atome wurden in kontinuierlich fließenden Elutionsmitteln gelöst, die durch drei aufeinander folgende Ionenaustauschersäulen gepumpt wurden.…”
Section: Experimentelle Technikenunclassified
“…Alle neueren experimentellen Studien, die jeweils im reinen F − ‐, Cl − ‐ und Br − ‐System durchgeführt wurden,204 stimmen ausgezeichnet mit den theoretischen Vorhersagen überein, die relativistische Effekte beinhalten 202. 205 Die Fluorid‐Komplexbildung von Db in 0.2 M HF wurde kürzlich in einem Experiment bestätigt, in dem drei aufeinander folgende Ionenaustauschersäulen eingesetzt wurden – eine Kationenaustauschersäule (Filter), eine Anionenaustauschersäule (Chromatographie) sowie eine weitere Kationenaustauschersäule (Filter) 163. Es wurde gezeigt, dass Db einen anionischen Fluorid‐Komplex bildet, der auf dem Anionenaustauscherharz stark zurückgehalten wird.…”
Section: Chemische Eigenschaftenunclassified
“…Several attempts to clarify chemical properties of Db in aqueous solution have been made by extraction and ionexchange chromatography methods [7][8][9][10][11][12][13]. Comparative studies of Db with its lighter homologues Nb and Ta, and the pseudo-homologue Pa were carried out.…”
Section: Introductionmentioning
confidence: 99%